Intelligent System and Computing - Yang (Cindy) Yi (IntechOpen, 2020)
The book'Intelligent System and Computing” reports the theory, mathematical models, algorithms, design methods, and applications of intelligent systems and computing. It covers various disciplines including computer and information science, electrical and computer engineering, natural sciences, economics, and neuroscience. The broad-ranging discussion covers the key disciplines in computational science and artificial intelligence as well as advances in neuromorphic computing, deep learning, the Internet of Things, computer vision, and many others. This volume provides both academics and professionals with a comprehensive overview of the field and presents areas for future research.